GROWTH PARAMETERS ESTIMATES OF PARREYSIA FAVIDENS (BENSON, 1862) FROM THE RIVER BURHI GANDAK IN BIHAR, INDIA - Chandravanshi, Sanjay; MOGALEKAR, HS; SAHIL; DUPARE, R.R.; SAHU, ADYASHA; CHANDRAN, SUDHAN; NYAK, S. K.; BRAHMCHARI, R.K.; SINGH, M. K. (Journal of the Inland Fisheries Society of India, 2025)
The study has been conducted to investigate the length-weight, width-weight relationship and condition factor (K) of the freshwater mussel Parreysia favidens, from the river Burhi Gandak, Bihar India. A total 520 specimens were collected during July 2020 to June 2021. The observed length of P. favidens was ranged from 30 to 80 mm and weight ranged from 3.01 to 30.09 g. The species showed negative allometric growth pattern. The total length-weight and width-weight relationships were W= 0.0002L2.472 and 0.00152.451 and the r2 value (coefficient of determination) was estimated at 0.644 and 0.599. The condition factor (K) was determined to be 0.75. All LWR regression parameters showed highly significant (P > 0.001). These results will provide the framework for the long-term conservation and management of the freshwater mussels’ resources in the Burhi Gandak River, North Bihar, India.